RSSI Analysis on CSS Modulation in the 433 MHz Frequency Band Using Lora in Flood Sensor - Ridwan Satrio Hadikusuma; Lela Nurpulaela (Jurusan Teknik Elektro UIN Sunan Gunung Djati Bandung, 2022)
Long Range (LoRa) low power is a transmission technology capable of connecting multiple sensors to the Internet of Things in the future. LoRa uses Chirp Spread Spectrum (CSS) frequency modulation which promises to achieve remote connectivity at very low power. More specifically, this paper focuses on the analysis of Receive Signal Strength Indicator (RSSI) on CSS modulation on flood sensors. This paper presents a detailed model of using LoRa on flood sensors, showing that LoRa is capable of transmitting sensor data over long distances with perfect RSSI values. The results showed the potential for a close communication range with a narrow band network at a frequency of 433 MHz and an average RSSI of -50 dB at a maximum distance of 600 meters without obstruction. Although LoRa communication uses CSS modulation and has good RSSI values, in long-distance communication with data in the form of video or large sensor data, this toughness is not sufficient due to long distances and large bandwidth usage, while in this study LoRa type Ai Thinker Ra- 02 SX 1278 can only be set up to 125 KHz according to the datasheet. The disadvantages of using large sensor data over long distances and a larger footprint make CSS vulnerable to other, possibly larger, resources.